2011
DOI: 10.1371/journal.pone.0017639
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cell Stress in Neurons from Transgenic Mice Expressing Yellow Fluorescent Protein: Implications for Neurodegeneration Research

Abstract: BackgroundMice expressing fluorescent proteins in neurons are one of the most powerful tools in modern neuroscience research and are increasingly being used for in vivo studies of neurodegeneration. However, these mice are often used under the assumption that the fluorescent proteins present are biologically inert.Methodology/Principal FindingsHere, we show that thy1-driven expression of yellow fluorescent protein (YFP) in neurons triggers multiple cell stress responses at both the mRNA and protein levels in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Similar observations were made with VN-βS and VN-γS (not shown). Fusion to VN approximately doubles the size of αS which may contribute to these alterations, as observed also with intact (full-length) fluorophores and corresponding fusion proteins [56][57][58]. These elevated levels of VN-αS protein were detected at early time points after transfection and sustained high throughout the duration of the experiments.…”
Section: Fusion Of Vn To Synuclein Results In Aberrant Protein Levelssupporting
confidence: 55%
“…Similar observations were made with VN-βS and VN-γS (not shown). Fusion to VN approximately doubles the size of αS which may contribute to these alterations, as observed also with intact (full-length) fluorophores and corresponding fusion proteins [56][57][58]. These elevated levels of VN-αS protein were detected at early time points after transfection and sustained high throughout the duration of the experiments.…”
Section: Fusion Of Vn To Synuclein Results In Aberrant Protein Levelssupporting
confidence: 55%
“…However, a recent study suggested that data from these mice should be interpreted with caution (Comley et al, 2011). The authors showed that YFP expression causes upregulation of stress markers in the spinal cord, and increases neurofilament staining in distal motor axons at the neuromuscular junction in otherwise normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was also reported that fluorescent proteins expressed in cells per tissues can modify their molecular composition and cellular activities. [22][23][24][25] These results suggest that GFP marker gene is not suitable for human gene therapy. Now, we are analyzing the effect of neonatal gene therapy for MLD using self-complementary AAV 9 vector expressing only ASA for clinical trial.…”
Section: Discussionmentioning
confidence: 99%